Reframing Seventeenth-Century Bolognese Art : Archival Discoveries - Morselli, Rafaella; Bohn, Babette, 1950- (Book collections on Project MUSE., 2019)
These ground-breaking essays, all based on original archival research, consider the evolving interest in Bolognese art in seventeenth-century Italy, particularly focusing on the period after the death of Guido Reni in 1642. Edited by Bolognese specialists Raffaella Morselli and Babette Bohn, the studies collected here focus on the taste for Bolognese art within Bologna itself and in other parts of the Italian peninsula, including Mantua, Ferrara, Rome, and Florence. Essays examine the roles of gender, class, and the social status of the artist in early modern Bologna; approaches to exhibiting artworks in noble Bolognese collections; the reputations of local women artists; the popularity of Bolognese quadratura painting; and the relative success of both contemporary and earlier Bolognese artists with Italian collectors.